Akselerasi Literasi Perpajakan dan Pendampingan Teknis Coretax System untuk Penguatan Self-Assessment di RS Puri Raharja - I Gusti Agung Prama Yoga; Desak Rurik Pradnya Paramitha Nida; Ida I Dewa Ayu Mas Manik Sastri (Community Service Journal (CSJ), 2026)
The implementation of the Coretax Administration System (CTAS) as part of Indonesia's digital tax transformation requires taxpayers' readiness to understand the technology-based tax administration system. However, low digital tax literacy and limited technical understanding of self-assessment mechanisms remain major obstacles, especially in institutions with high work mobility, such as hospitals. This community service activity aims to increase digital tax literacy and provide technical assistance with tax reporting using the Coretax System for Puri Raharja Hospital employees. The implementation method uses a participatory empowerment approach in three stages: seminars, assistance with filling out the Coretax for personal accounts, and follow-up consultation. The implementation will be carried out at Puri Raharja Hospital, Denpasar, in March 2026. Tax literacy seminars, technical workshops, and the opening of the "Tax Corner" were conducted to provide on-site assistance to medical personnel, administrative staff, and hospital management. The material provided includes the integration of NIK into NPWP, the operation of the Coretax portal, independent data validation, and simulation of reporting Annual Tax Returns forms 1770S and 1770. The results of the activity showed an increase in participants' understanding of the Coretax System, an increase in their ability to report taxes independently, and an increase in awareness of the importance of digital tax compliance. However, there are still obstacles, including application errors and a lack of readiness. This program is expected to foster a more adaptive, accurate, and timely tax compliance culture within Puri Raharja Hospital while advancing the transformation of national tax administration in the digital era.